2019
DOI: 10.1115/1.4042902
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Optimizing the Compliance of Multilayered Biomimetic Tissue Engineered Vascular Grafts

Abstract: Coronary artery bypass grafts used to treat coronary artery disease (CAD) often fail due to compliance mismatch. In this study, we have developed an experimental/computational approach to fabricate an acellular biomimetic hybrid tissue engineered vascular graft (TEVG) composed of alternating layers of electrospun porcine gelatin/polycaprolactone (PCL) and human tropoelastin/PCL blends with the goal of compliance-matching to rat abdominal aorta, while maintaining specific geometrical constraints. Polymeric blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…While the clinical trials arose from trial-anderror empirical approaches, computational models have also become increasingly sophisticated and recognized as tools for guiding the design of implants for tissue engineering applications. 22,30 Thus, we sought to exploit the advances in computational modeling to establish a new approach to scaffold design. We previously showed that computational models can describe 6 and predict 9 in vivo neovessel development that starts from a biodegradable polymeric scaffold implanted as an IVC-interposition model, a reasonable surrogate for an extracardiac Fontan conduit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the clinical trials arose from trial-anderror empirical approaches, computational models have also become increasingly sophisticated and recognized as tools for guiding the design of implants for tissue engineering applications. 22,30 Thus, we sought to exploit the advances in computational modeling to establish a new approach to scaffold design. We previously showed that computational models can describe 6 and predict 9 in vivo neovessel development that starts from a biodegradable polymeric scaffold implanted as an IVC-interposition model, a reasonable surrogate for an extracardiac Fontan conduit.…”
Section: Discussionmentioning
confidence: 99%
“…with R 2 the luminal radius at pressure P 2 and R 1 that at P 1 , is an important clinical and previously identified computational metric 22 that can be used to minimize the mechanical mismatch between graft and adjacent vessels and thus promote normal hemodynamics. Since evolving thickness affects radial changes during loading, compliance quantifies the structural stiffness of the construct.…”
Section: Objective Function Formulationmentioning
confidence: 99%
“…Such endothelialization modality requires a strong binding between the circulating cell and the graft surface, which may be offered by progenitor-specific antibodies or ligand (Lu et al, 2013;Hao et al, 2020) or adhesive peptides (Choi et al, 2016;Hao et al, 2017;Liu et al, 2021) immobilized on the lumen surface. Since all three in situ mechanisms are still insufficient to create a continuous endothelium throughout a long vascular graft in human patients, ex vivo or in vitro seeding of matured vascular cells (Dahan et al, 2017), progenitor/stem cells (Olausson et al, 2012;Ardila et al, 2019), or genetically modified autologous cells expressing fibulin-5 and VEGF, onto the graft lumen have been employed (Sánchez et al, 2018).…”
Section: Biological Functionalization Of a Graft For Vascular Regener...mentioning
confidence: 99%
“…The neotissue growth and graft remodeling in turn change the flow-graft interactions. Therefore, computational models simulate such interactions as well as advanced statistical analyses of a parametric cause-effect relationship have been exploited to accelerate the rational optimization of vascular grafts ( Keshavarzian et al, 2019 ; Tamimi et al, 2019 ; Khosravi et al, 2020 ). Recently, data-informed models have been developed to improve graft designs, even toward patient-specific design ( Best et al, 2018 ), for desired graft performances in terms of lumen diameter, extracellular matrix (ECM) production, and levels of inflammation ( Best et al, 2019 ; Drews et al, 2020 ).…”
Section: Counteracting Adverse Remodeling With Regenerative Signalsmentioning
confidence: 99%
“…Computational modeling has shown promise for accelerating the optimization process of vascular grafts by determining potential mechanisms of neotissue formation and effects of altering scaffold parameters. [17,18] Recent models informed by experimental data have suggested that in vivo neovessel formation is an inflammation-driven, mechano-mediated process. [15] Therefore, altering the design of the scaffold provides a twofold means for optimizing in vivo performance.…”
Section: Introductionmentioning
confidence: 99%